Human and mouse cortical astrocytes: a comparative view from development to morphological and functional characterization - Degl’Innocenti, Elisa; Dell’Anno, Maria Teresa (Frontiers in Neuroanatomy, 2023)
The vision of astroglia as a bare scaffold to neuronal circuitry has been largely overturned. Astrocytes exert a neurotrophic function, but also take active part in supporting synaptic transmission and in calibrating blood circulation. Many aspects of their functioning have been unveiled from studies conducted in murine models, however evidence is showing many differences between mouse and human astrocytes starting from their development and encompassing morphological, transcriptomic and physiological variations when they achieve complete maturation. The evolutionary race toward superior cognitive abilities unique to humans has drastically impacted neocortex structure and, together with neuronal circuitry, astrocytes have also been affected with the acquisition of species-specific properties. In this review, we summarize diversities between murine and human astroglia, with a specific focus on neocortex, in a panoramic view that starts with their developmental origin to include all structural and molecular differences that mark the uniqueness of human astrocytes.